IMPLEMENTASI KEBIJAKAN TATALAKSANA PENYELENGGARAAN PELAYANAN JASA TERMINAL TYPE A INDIHIANG KOTA TASIKMALAYA - Astri Fatimah (Jurnal Administrasi Publik, 2016)
This study sought to examine the implementation of the policy of conducting ofTatalaksana Type A Terminal Services Indihiang the town of Tasikmalaya. The problemthat the credibility or trust of the community to the existence of the terminal Indihiangfelt still less. Example: passengers are more likely to wait in a certain pool/agentsoutside terminals rather than having to wait in the terminal Indihiang. One of thecauses of these problems result from poor management and weak organization of theexecutor in finding solutions to solve these problems. This research uses qualitativedeskriptip to describe an event. This approach, looking at that one event must beunderstood holistically with mengutakaman process rather than results. The techniqueof data collection was done through interviews, observation and the study oflibrarianship. Technical data analysis using data reduction steps, the presentation ofdata, and the withdrawal of the conclusion. Based on the results of field research,obtained information that the Policy Implementation Tatalaksana Type A TerminalService Organization of Indihiang town of Tasikmalaya has not been as expected. Needfor evaluation and sit together between various stakeholders in order to Type AIndihiang Terminal town of Tasikmalaya to function in accordance with the allocation.So these government assets can give a large contribution to development in the town ofTasikmalaya.